Hubungan Peran Orangtua dengan Perilaku Sosial Emosional Anak Prasekolah Menggunakan Gadgetdi Singkil - Septiya , Winda; Sutanta; Kurniawati , Emy (HEALTHY BEHAVIOR JOURNAL, 2023)
Background of Study: Technological developments that are very influential on the human mindset are gadgets. The use of gadgets has positive and negative impacts, one the gadget consumers start from early childhood, so it requires the role of parents for the readiness and development of their children, social and emotional abilities are the foundation for the development of the ability to interact with the wider environment.Purpose: This study aims to determine whether there is a relationship between the role of parents and the emotional and social behavior of preschool children who use gadgets in Singkil.Method: This study uses an analytical survey method with a cross-sectional approach and the data collection techniques with questionnaires. The sampling technique used a total sampling of 39 respondents. The data were processed by SPSS to analyze univariate and bivariate with the Spearman Rank correlation test.Result: Data collection was carried out in April-May 2022 with 39 samples. The results show that the role of parents is sufficient at 61.5%, and the value of social-emotional behavior of preschool children is sufficient at 56.4%. The results of the Spearman rank correlation test showed that the p-value was 0.004 (p <0.05), and the correlation coefficient value of the two variables was moderate (0.452).Conclusion: Based on the results of the study, it can be concluded that there is a relationship between the role of parents and the emotional and social behavior of preschool children who use gadgets in Singkil village with a p-value of 0.004.